2019
DOI: 10.3390/nu11112606
|View full text |Cite
|
Sign up to set email alerts
|

Combined Buckwheat d-Fagomine and Fish Omega-3 PUFAs Stabilize the Populations of Gut Prevotella and Bacteroides While Reducing Weight Gain in Rats

Abstract: Some functional food components may help maintain homeostasis by promoting balanced gut microbiota. Here, we explore the possible complementary effects of d-fagomine and ω-3 polyunsaturated fatty acids (ω-3 PUFAs) eicosapentaenoic acid/docosahexaenoic acid (EPA/DHA 1:1) on putatively beneficial gut bacterial strains. Male Sprague–Dawley rats were supplemented with d-fagomine, ω-3 PUFAs, or both, for 23 weeks. Bacterial subgroups were evaluated in fecal DNA by quantitative real-time polymerase chain reaction (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
(71 reference statements)
3
9
0
Order By: Relevance
“…This shift towards a lower inflammatory state described by fatty acid profiles and lipid mediators’ synthesis in ω-3 PUFAs supplemented groups compared with controls was highly in agreement with the lower values of plasma IL-6, leptin and balance AST/ALT reported in the liver ( Table 1 ) ( 20 , 24 ). Additionally, this anti-inflammatory condition attributed to supplementation with fish oils was associated with decreased lipid deposition in plasma and organs, and the lower plasma insulin values for 67% of the rats fed the HFHS diet.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This shift towards a lower inflammatory state described by fatty acid profiles and lipid mediators’ synthesis in ω-3 PUFAs supplemented groups compared with controls was highly in agreement with the lower values of plasma IL-6, leptin and balance AST/ALT reported in the liver ( Table 1 ) ( 20 , 24 ). Additionally, this anti-inflammatory condition attributed to supplementation with fish oils was associated with decreased lipid deposition in plasma and organs, and the lower plasma insulin values for 67% of the rats fed the HFHS diet.…”
Section: Resultssupporting
confidence: 85%
“…Such reduction was especially relevant for HFHS-fed rats supplemented with w-3 PUFAs which showed general fat content in plasma, liver, kidney, skeletal muscle and adipose tissue similar to the STD rats. These findings are in agreement with the histological liver steatosis as we previously reported in the same cohort of rats (24).…”
Section: Insulin Resistance Ectopic Lipid Deposition and Low-grade Inflammationsupporting
confidence: 94%
See 1 more Smart Citation
“…Previous studies reported that EPA and DHA significantly increased the abundances of Firmicutes (Lactobacillus genus) and Bifidobacteria in mice fed an HFD [106,107]. According to the authors, the dfagomine and ω-3 PUFAs combination group gained less weight compared to the controls and the ω-3 PUFAs group, and the combination helped maintain the relative populations of Bacteroides and Prevotella in the rat intestinal tract, providing the anti-inflammatory and cardiovascular benefits of ω-3 PUFAs [108]. It is well known that tartary buckwheat is rich in flavonoids, and dietary rutin or quercetin in buckwheat can ameliorate lipid metabolism, whereas buckwheat-resistant starch may also have beneficial effects on lipid metabolism.…”
Section: Effects On Obesitymentioning
confidence: 96%
“…We later suggested that the action of d -fagomine on some microbial populations might explain, at least in part, its functional effect against fat-induced impaired glucose tolerance and hepatic inflammation [ 7 ]. d -Fagomine has the capacity to stabilize levels of putatively beneficial gut bacteria (e.g., the Bacteroidetes phylum, Bifidobacteriales order, and Prevotella genus) in normal rats fed a standard diet for an extended period of time [ 8 , 9 ]. When combined with fish omega-3 polyunsaturated fatty acids (PUFAs), d -fagomine has an early effect compatible with fast changes in bacterial composition, while the protective anti-inflammatory action of PUFAs appears to be less related to changes in gut microbiota [ 9 ].…”
Section: Introductionmentioning
confidence: 99%